Highly Selective and Pollution‐Free Electrochemical Extraction of Lithium by a Polyaniline/LixMn2O4 Cell. Issue 7 (8th March 2019) - Zhao, Along; Liu, Jincheng; Ai, Xinping; Yang, Hanxi; Cao, Yuliang
Abstract: Conventional lithium extraction processes are inefficient or inadaptable for application in salt‐lake brines with high Mg/Li ratios of ≥6. A new electrochemical cell, polyaniline (PANI)/Li x Mn2 O4, was proposed to solve this problem for selective recovery of Li + ions from brine water with high impurity cations (K +, Na +, Mg 2+, etc). Benefiting from the unique selectivity of spinel Li x Mn2 O4 for Li + insertion and the high capacity of the PANI polymer for Cl − doping, this PANI/Li x Mn2 O4 cell could simultaneously extract LiCl from a simulated brine with a high average current efficiency of 95 %, an energy consumption of 3.95 W h molLiCl −1, and a strong cycle ability with 70.8 % capacity retention over 200 cycles. In particular, this method avoids the use of additional chemicals, offering a highly efficient, pollution‐free technology for Li + extraction from brine waters. Abstract : Lithium extraction : A new polyaniline (PANI)/Li x Mn2 O4 cell is proposed for the recovery of Li from brines with high Mg/Li ratios. Benefiting from the high selectivity of the spinel Li x Mn2 O4 positive electrode for Li + insertion and the high efficiency of the PANI negative electrode for the capture of Cl − ions, it offers a potential application for the direct recovery of LiCl from brine lakes with high Mg/Li ratios.